Identifying employees at risk for job loss during sick leave. (October 2013) - Flach, Peter A.; Groothoff, Johan W.; Bültmann, Ute
Abstract Purpose: To examine the associations between medical, work-related, organizational and sociodemographic factors and job loss during sick leave in a Dutch population of 4132 employees on sick leave. Methods: Data were assessed by occupational health physicians (OHPs) on sociodemographic, medical, work-related and organizational factors. Odds ratios for job loss were calculated in logistic regression models. Results: Job loss during sick leave is associated with mental disorder, a history of sick leave due to these disorders, lack of co-worker and supervisor support, job insecurity and working as a civil servant or a teacher. Associations vary for gender and for company size. Conclusions: Job loss during sick leave is associated with medical, work-related, organizational and socio-demographic factors. The findings of this study might help the OHP or other health professionals involved in the management of employees on sick leave to identify those employees who are at risk for job loss during sick leave, and might help policymakers to decide on priorities in prevention and treatment. Future studies should have a longitudinal, prospective design and include information about the type of contract, possible causes for job loss, severity and treatment of the disorder causing the sick leave. Implications for Rehabilitation The labor market moves to more and more flexible and temporary contracts. This leads to more precarious types of employment. The risk of job loss during sick leave is associated with medical, work-related, organizational and sociodemographic factors. Occupational health physicians and other professionals in the field of work rehabilitation should be aware of these associations to prevent job loss due to these factors.